Detection of jeilongvirus circulation in Finnish urban rat populations by a novel pan-jeilong-RT-qPCR - Pulkkinen, Emilia; Sippola, Ella; Sgarabotto, Elena; Suomalainen, Nina; Lilley, Thomas; Meierhofer, Melissa B.; Aivelo, Tuomas; Zöldi, Viktor; Sallinen, Suvi; Smura, Teemu; Henttonen, Heikki; Huitu, Otso; et al. (Elsevier, 2026)
Paramyxoviruses can infect a variety of host species and cause infections among wildlife and humans. Some of these viruses can also cause severe zoonotic infections. Although new paramyxoviruses, such as jeilongviruses, are being recognized, little is known about their host species variation and pathogenesis. The current screening methods to detect paramyxoviruses are either laborious conventional PCR methods or costly next-generation sequencing methods. Therefore, we designed a new pan-jeilong-RT-qPCR assay to detect jeilong- and parajeilongviruses from wildlife samples and screened rat, shrew, and bat samples from Finland and Latvia. With this new real-time PCR assay, we detected jeilongviruses in Finnish urban rat populations during 2020–2023 with a 13% positivity rate, including beilong virus (Jeilongvirus beilongi). This finding highlights the abundance of jeilongvirus in rats and the need for continued surveillance and more detailed characterization of these novel pathogens to evaluate the zoonotic potential of these viruses in rat and other rodent populations.
Keywords: paramyxovirus; jeilongvirus; parajeilongvirus; Finland; Latvia; real-time PCR; rat